Islamic Political Ethics in Student Organizations: Actualization of Al-Mawardi’s Leadership Values in the Muhammadiyah Student Association of Central Kalimantan - Siti Rodiah; Diana Dwi Andriani; Naufal Naufal (Civilization Research: Journal of Islamic Studies, 2026)
Contemporary Islamic student organizations increasingly face challenges of political pragmatism, ethical decline and internal organizational conflict, highlighting the need for value-based leadership. Although Islamic political ethics have been widely discussed from normative and conceptual perspectives, empirical evidence on the implementation of Al-Mawardi’s leadership values within Islamic student organizations remains limited. This study aims to analyze the actualization of Al-Mawardi’s political ethics in the Regional Executive Board of the Muhammadiyah Student Association (DPD IMM) of Central Kalimantan. A qualitative case study was conducted using participant observation, semi-structured interviews, document analysis, and thematic content analysis. The findings demonstrate that the principles of alanah (trustworthiness), 'ada (justice), shūrā (consultation), and mas'ūliyyah (accountability) are embedded in OG, PD, cadre development, and CR. Rather than functioning solely as normative ideals, these values shape ELP practices that strengthen organizational integrity, collective responsibility and participatory governance. This study confirms the relevance of Al-Mawardi’s political thought in addressing contemporary leadership challenges within Islamic student organizations. Its principal contribution lies in providing empirical evidence that bridges classical Islamic political ethics with contemporary organizational leadership, thereby extending the application of Al-Mawardi’s framework into organizational practice in the Indonesian context beyond normative discourse.